Textbook Evaluation: How does It Assist Intercultural Communicative Competence? - Sri Novianti; Yanty Wirza (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2024)
Language learning is culture-bound, so culture should be included in the process of language teaching and learning. Using the framework proposed by Cortazzi and Jin (1999), this study evaluates the potential use of the textbook English on Sky to assist Intercultural Communicative Competence in Instruction as evidenced by the occurrence of three types of cultural elements: source culture, target culture, and international culture contained in the textbook. Conducted in Islamic boarding school context, this descriptive study collected data through a checklist from Cortazzi and Jin (1999), questionnaires distributed to students, and an interview conducted to an English teacher using the textbook. The findings reveal that the textbook contains all types of cultural elements represented in reading texts, dialogues, pictures, and tasks. Even though the occurrence of each is not balanced, English on Sky has potential to assist Intercultural Communicative Competence in Instruction since all types of cultures contained do not conflict with the value of the Islamic context. Pedagogically, teachers can use the textbook as the main source for teaching materials in Islamic schools so that students’ Intercultural Communicative Competence can be enhanced.